2021
DOI: 10.1002/bies.202100093
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 and ferroptosis: Regulatory mechanisms and therapeutic potential

Abstract: Ferroptosis, a form of regulated cell death triggered by lipid hydroperoxide accumulation, has an important role in a variety of diseases and pathological conditions, such as cancer. Targeting ferroptosis is emerging as a promising means of therapeutic intervention in cancer treatment. Polyunsaturated fatty acids, reactive oxygen species, and labile iron constitute the major underlying triggers for ferroptosis. Other regulators of ferroptosis have also been discovered recently, among them the mechanistic targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 95 publications
0
36
0
Order By: Relevance
“…Hence, oxidative stress has become a critical linking between ferroptosis and neurological disorders. Up to now, the inhibitors and activators of ferroptosis [9][10][11][12][13][14], as well as other involved signaling pathways [15][16][17], have been widely studied. Furthermore, the mediators of oxidative stress might become a potential therapeutic target for the treatment of neurological disorders by regulating the process of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, oxidative stress has become a critical linking between ferroptosis and neurological disorders. Up to now, the inhibitors and activators of ferroptosis [9][10][11][12][13][14], as well as other involved signaling pathways [15][16][17], have been widely studied. Furthermore, the mediators of oxidative stress might become a potential therapeutic target for the treatment of neurological disorders by regulating the process of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the iron phenotypic defects were reported to be rescued by the over-expression of the human nucleoside diphosphate kinase Nm23-H4 targeted to the mitochondrial matrix, where it converts GDP to GTP using ATP as phosphate donor [ 4 ]. Despite some evidence about the link between mitochondrial iron homeostasis and the TOR pathway in yeast and mammals [ 15 , 16 , 17 ], the relationship between mitochondrial iron, guanine nucleotides content and TOR pathway remains to be elucidated. In the present study, it was demonstrated that citrate regulates Ggc1p by trans-activating the uniport of GTP into the mitochondria, suggesting a role of citrate in the homeostasis of the guanine nucleotide pool in the mitochondrial matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is an iron‐dependent form of regulated cell death that results from oxidative damages of membrane phospholipids, and is mechanistically and morphologically unique compared to other cell death modalities, such as apoptosis and necroptosis [1]. Excessive ferroptosis is indicative of many pathological conditions, including cardiovascular diseases, neurodegenerative diseases, and acute organ injury, whereas ferroptosis impairment has been shown to fuel tumor progression and metastasis; therefore, targeting ferroptosis represents a promising strategy for treating these diseases [2–10]. Ferroptosis is triggered by a lethal accumulation of lipid peroxides on the cell membrane.…”
Section: Figurementioning
confidence: 99%